Leadership in the Media Industry: Theoretical Approach - Londoño-Proaño, Cristian (2021)
The digital transformation created dramatic and important changes in the media industry. The content is saturated and consumption patterns have varied. Therefore, the audience migrated from traditional means to digital patterns, which has caused the sale and merging of the media. Every day business models for the media industry are integrated by new actors and dynamics. Leadership, innovation, and creativity are some of the alternatives which the media can rely on to make the most of the opportunities generated by the digital transformation. Leadership is a process of influence that seeks to achieve common goals. The media industry has been widely studied by psychologists, philosophers, historians, management theorists, scientists, politicians, educators, philosophers, biologists, and geneticists. The media industry is recognized by opinion formers such as Rupert Murdoch or Greg Dyke. Hence, this article is aimed to do a theoretical review of the latest researches on leadership in the media industry. It has been evidenced that little literature on leadership in the media industry has been done. It is established that human resources play an important role in the changing and competitive landscape of the media industry and it is determined that people need to be prepared to achieve the only competitive advantage which is innovation. In this context, innovation is addressed as long as the leadership style promotes changes and acts quickly in a very timely manner. Some authors point out that the most effective leadership style in industries is transformational leadership since it positively influences followers with motivation and inspiration provoking the achievement of the organizational goals, which exceed the selfish objectives set by followers. In addition, it is aimed to promote dialogue and to get the commitment. Thus, the importance of media leaders managing people and tasks